Geochemical speciation and risk assessment of metals in sediments of the Lobo-Broa Reservoir, Brazil. Issue 3 (10th April 2017) - Cervi, Eduardo Cimino; Fernandes, Felippe; Miranda, Renato Billia de; Mauad, Frederico Fábio; Michalovicz, Leandro; Poleto, Cristiano
Abstract : Purpose: Brazilian sediment quality criteria were established based on pseudo-total metal contents, which is not suitable to determine their bioavailability and the ecological risk for aquatic biota. Therefore, the geochemical speciation of five metals (Cu, Fe, Ni, Pb and Zn) was determined to assess the distribution and ecological risk of sediments in a tropical shallow reservoir from Brazil. The paper aims to discuss these issues. Design/methodology/approach: A survey of metals in ten representative stations of surface sediments (0-20 cm) from Carlos Botelho (Lobo-Broa) Reservoir was conducted during the dry season in April 2014. Sediment parameters were measured in situ. The geochemical speciation of metals was carried out using the modified three-stage BCR-701 procedure (Davutluoglu et al., 2011) and compared with pseudo-total metal contents. Findings: Contamination at S-1 and S-8 was more severe than other sampling sites, especially for Cu, Ni, Pb and Zn. Metals such as Cu, Ni and Zn occasionally may be associated with adverse biological effects based on the comparison with sediment quality guidelines. The risk assessment code suggests no risk for Fe and low risk for Cu and Ni. Originality/value: Geochemical speciation of metals could be useful in developing effective management strategies to control metal pollution in the Lobo-Broa Reservoir. Substantial amounts of Pb (classified as medium risk) were bound to humic substances and/or insoluble metal sulfides, and could pose serious risk to the benthic community through the food chain. Zinc at S-1, S-3 and S-8 showed high risk, indicating that an appreciable portion of Zn could be available to aquatic biota.